The Influence of Royal Institution Factor and Patriotism in Youth National Indexes of Malaysia - Wahab, ``Samsudin (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
The concern in our society today is to strengthening of identity amongst the youth. This concern is due to the characters ofyouth who is more curious and love to try new things, hence easily misled. The present youth is our hope for the future togovern our country. This paper studies the strength level of identity amongst youth in Malaysian selective public andprivate higher educational institutions. The identity components measured in this study are royal institution acceptanceand patriotism contribution towards national indices in Malaysia. The manifestation of each component was analyzed via knowledge, behavior, emotion, value, and belief. This study was designed to utilize a quantitative approach with surveymethod. A survey questionnaire was constructed as a research instrument to collect data for this study, and an identitymeasurement tool was also developed by this group of researchers. The participants are 456 male and 603 female students from sixth selective higher institution with different years and streams of studies as well as ethnics. The studyfound that the mean for patriotism 4.16, royal institution (4.62), which make the indexes encourage able in Malaysia. In addition, there was a significant difference between ethnics (p<0.05). In conclusion, the strength level of identity found bythis study is alarming.